Burning mouth syndrome (BMS) - possible pathogenesis related to pain pathways - Elena Claudia Coculescu; Gheorghe Manole; Bogdan-Ioan Coculescu (Romanian Journal of Medical Practice, 2023)
Burning mouth syndrome (BMS) has been admitted relatively recently as a condition/syndrome within oral pathology, bordering various other medical specialties, which may collaborate to determine the diagnosis and especially to achieve therapeutic success. From a clinical point of view, BMS can present itself in 2 forms: the primary/essential form, whose etiopathogenesis is unexplained, justifying the permanent concern as a topic of research at the international level, and the secondary form, in which the causes of the syndrome can be identified and treated/ removed, allowing healing. Particular to the primary form of BMS is the discrepancy between the extent of subjective pain felt by the patient as “burning” and the lack of any objective (clinical) signs in the oral mucosa. In this form of BMS, the pathogenesis of pain can be explained by invoking the role and importance of the field and some favorable factors. In recent years it has been noticed that changes in taste perception and pain tolerance could be possible causes of the “burning” sensation. Thus, the involvement of the field allowed the following hypothesis to be issued, namely that taste is generated mainly at the level of the fungiform lingual papillae.